Effect of a Motivational Interviewing-Based Health Coaching on Quality of Life in Subjects With COPD - Rehman, Hamid (Respir Care, 2017)
BACKGROUND: Improving quality of life (QOL) is a key goal in the care of patients with COPD. Pulmonary rehabilitation (PR) has clearly been shown to improve QOL, but is not accessible to many eligible patients. There is a need for alternative programs designed to improve patient well-being that are accessible to all patients with COPD. Our goal was to pilot test a simple, telephone-based health-coaching intervention that was recently shown to decrease readmission among hospitalized COPD patients and stable COPD patients eligible for PR. METHODS: Subjects received a 3-month intervention consisting of 10 health-coaching telephone calls based on motivational interviewing principles. Outcome measures included dyspnea level, measured by the modified Medical Research Council scale, and QOL, measured by the Chronic Respiratory Questionnaire and a single-item general self-rated health status. RESULTS: Fifty subjects with moderate to severe COPD were enrolled in the study. Forty-four subjects (86%) completed the study intervention. Dyspnea measured by the modified Medical Research Council score improved significantly after the intervention (P = .002). The domains of fatigue, emotional function, and mastery on the Chronic Respiratory Disease Questionnaire and the single-item QOL question also improved significantly after the 3 months of health coaching (P = .001, P = .001, P = .007, and P = .03, respectively). Thirty-six (71%) subjects had a clinically meaningful improvement in at least 1 study end point (either in the severity of dyspnea or a domain of QOL). Thirty subjects (58%) had an improvement of ≥0.5 points, the minimum clinically important difference in at least 1 component of the Chronic Respiratory Disease Questionnaire. CONCLUSIONS: A telephone-delivered motivational interviewing-based coaching program for COPD patients is a feasible, well-accepted (by both participants and providers), simple, and novel intervention to improve the well-being of patients with COPD. This pilot study provides insight into a possible alternative to a conventional PR program for patients with limited access to that program.